Neurodevelopmental disorders in children seeking obesity treatment- associations with intellectual ability and psychiatric conditions - Dellenmark-Blom, Maria; Järvholm, Kajsa; Sjögren, Lovisa; Levinsson, Anna; Dahlgren, Jovanna (Frontiers in Psychiatry, 2024)
Background Neurodevelopmental disorders (NDD), psychiatric comorbidity and cognitive deficits are commonly seen in children with obesity; however, little is known about the overlap between these conditions. This study aimed to examine the undiagnosed and diagnosed frequency of NDDs and explore its association with psychiatric conditions and general intellectual ability (IQ) in children presenting for obesity treatment. Methods In this observational study at two outpatient obesity clinics during 2018-2019, 80 children (8-17 years) were consecutively recruited, and screened for NDD unless already diagnosed with an NDD. A psychiatric unit evaluated children who screened positive for NDD. Diagnoses and clinical background factors were collected from medical records. IQ was assessed with the Weschler Intelligence Scales and internalizing symptoms were assessed using the Beck Youth Inventories. Associations between background factors, IQ and internalizing symptoms were explored in relation to having an NDD or not. Results We found that 47/80 children had at least one NDD. Children with a diagnosed NDD before study start (n = 30) had significantly more comorbidities than children diagnosed after the study screening (n = 17) (P = .01). Greater cognitive impairment was seen in children with NDD compared with children without an NDD (P = .01). Also, 33/73 participants self-reported substantial internalizing symptoms. At follow-up, 21/79 participants, in addition to NDD, had been diagnosed with another psychiatric disorder. Ten of these were children that had been diagnosed with an NDD before study start. Conclusion The overlap between NDD, cognitive deficits and psychiatric conditions in children with obesity is an important consideration for clinical practice. Screening for these conditions may be necessary when providing targeted interventions.